2019
DOI: 10.1002/cctc.201901827
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Enzyme Engineering Unveiled Unexpected Patterns of Halogenase Stabilization

Abstract: Halogenases are valuable biocatalysts for selective CÀ H activation, but despite recent efforts to broaden their application scope by means of protein engineering, improvement of thermostability and catalytic efficiency is still desired. A directed evolution campaign aimed at generating a thermostable flavindependent tryptophan 6-halogenase with reasonable activity suitable for chemoenzymatic purposes. These characteristics were tackled by combining successive rounds of epPCR along with semi-rational mutagenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 66 publications
2
42
0
2
Order By: Relevance
“…The same might be the case for Xcc4156. The presence of the same dimer in all Trp halogenase crystals, and in solution in the case of PrnA as observed by SEC (Dong et al, 2005), suggests an evolutionary advantage of this association, which is supported by a study on Thal mutants in which increased thermostability coincided with a higher proportion of the protein being present as a homodimer in solution (Minges et al, 2020).…”
Section: Crystal Structure Of Xcc4156mentioning
confidence: 60%
See 1 more Smart Citation
“…The same might be the case for Xcc4156. The presence of the same dimer in all Trp halogenase crystals, and in solution in the case of PrnA as observed by SEC (Dong et al, 2005), suggests an evolutionary advantage of this association, which is supported by a study on Thal mutants in which increased thermostability coincided with a higher proportion of the protein being present as a homodimer in solution (Minges et al, 2020).…”
Section: Crystal Structure Of Xcc4156mentioning
confidence: 60%
“…In Thal, a tryptophan halogenase, SEC and DLS also hinted towards a monomer, as is the case here, but the enzyme likewise formed a dimer in the crystal . ESI-MS under native conditions revealed that Thal was present both as a homodimer and a monomer in solution (Minges et al, 2020). The same might be the case for Xcc4156.…”
Section: Crystal Structure Of Xcc4156mentioning
confidence: 69%
“…To improve the utility of promiscuous enzymes, studies have implemented rational enzyme engineering, directed evolution and synthetic biology to assess and improve substrate scope (Glenn et al, 2011;Payne et al, 2015;Shepherd et al, 2015;Neubauer et al, 2020), regio-specificity (Lang et al, 2011;Andorfer et al, 2016;Shepherd et al, 2016;Moritzer et al, 2019), stability (Payne et al, 2013;Poor et al, 2014;Minges et al, 2020) and activity (Andorfer et al, 2016(Andorfer et al, , 2017Kong et al, 2020) of FDH halogenases (Table 3). Of particular interest are a study deploying directed evolution to yield RebH variants targeting positions 5, 6, and 7 of tryptamine (Andorfer et al, 2016), which could help to avoid the tryptophan decarboxylase bottleneck, and a study in which the substrate specificity of RebH was evolved to target, albeit with lower activities, "latestage" MIAs such as the yohimbines (Payne et al, 2015), which may allow promiscuity requirements to be eschewed entirely.…”
Section: New-to-nature Monoterpenoid Indole Alkaloidsmentioning
confidence: 99%
“…Andorfer et al, 2017 ThaL mutant (V52I, V82I, S360T, G469S, and S470N) with switched activity from a position 6 to a position 7 tryptophan halogenase. Moritzer et al, 2019 Thermostable ThaL mutant (S359G, K374L, I393V) with improved activity at 25 C. Minges et al, 2020 Bifunctional fusion enzyme consisting of a reductase (Fre) and a halogenase (XanH) showed slightly elevated halogenase activity in vitro compared to the two-component system.…”
Section: Brief Description Referencesmentioning
confidence: 99%
“…Moreover, a crucial site with a strong effect on substrate selectivity was also identified. The single mutant Thal-S359G showed a distinct preference towards L-tryptophan, and only 17% bromination of D-tryptophan was observed compared to >99% in the case of the wildtype enzyme [55]. In a complementary approach to identify thermostable halogenases, the Micklefield group identified a thermophilic tryptophan halogenase (Th-Hal) from a thermophilic and halotolerant strain of Streptomyces via computational genome mining.…”
Section: Protein Overexpression and Stabilizationmentioning
confidence: 99%